The influence of telmisartan on metformin pharmacokinetics and pharmacodynamics - Jiagen Wen; Meizi Zeng; Zhaoqian Liu; Honghao Zhou; Heng Xu; Min Huang; Wei Zhang (Elsevier, 2019)
Metformin is the most widely used drug among type 2 diabetes mellitus patients. However, drug interaction on metformin will influence its glucose-lowering effect or increase its side effect of lactic acidosis. In this study, a randomized, two-stage, crossover study was conducted to unveil the potential drug interaction between metformin and the anti-hypertension drug, telmisartan. Totally, 16 healthy Chinese male volunteers were enrolled. Blood samples from various time-points after drug adminstration were analyzed for metformin quantification. Oral glucose tolerance test (OGTT) was conducted 2 h after metformin administration. The AUC0-12 and Cmax of metformin in subjects co-administrated with telmisartan were significantly lower than with placebo. The geometric mean ratios (value of metformin plus telmisartan phase/value of metformin plus placebo phase) for Cmax and AUC0-12 is 0.7972 (90%CI: 0.7202-0.8824) and 0.8336 (90%CI: 0.7696-0.9028), respectively. Moreover, telmisartan co-administration significantly increased the plasma concentrations of both glucose and insulin at 0.5 h since OGTT (7.64 ± 1.86 mmol/l·min vs 6.77 ± 0.83 mmol/l·min, P = 0.040; 72.91 ± 31.98 μIU/ml·min vs 60.20 ± 24.20 μIU/ml·min, P = 0.037), though the AUC of glucose and insulin after OGTT showed no significant difference. These findings suggested that telmisartan had a significant influence on the Pharmacokinetics of metformin in healthy groups, though the influence on glucose-lowering effect was moderate. Keywords: Telmisartan, Metformin, Pharmacokinetics, Pharmacodynamics, Drug-drug interaction